(untitled) (Sociologisk Forskning, 1994)
Societal spheres in the light of history A division of society into statecraft, economy, and civil society is found in Plato’s Republic. Its theoretical base is the differentiated and sometimes contradictory norms for these spheres. The mainstream of European structuration is traced from the ’two swords’ - state and church - that structured western European society in the Middle Ages to the six societal spheres (or cardinal institutions) of society - the economy, government, science, religion, ethics, and art - that are visible today. Each maintain a large measure of independence (Weber’s Eigengesetzlichkeit). Each is dependent on a special type of freedom: civic liberties, free trade, academic freedom, religious toleration, the right to follow one’s conscience, artistic license. The paper pauses in this differentiation process at special junctures: the English revolution, the emergence of the Latin American and North American societies, the evolution of modem society as an underpinning of democracy, the emergence of the European Union, and the post-Communist Central and Eastern Europe.